Effect of repetitive transcranial magnetic stimulation on depression and cognition in individuals with traumatic brain injury: a systematic review and meta-analysis - Ping-Yen Tsai (Nature Portfolio, 2021)
Abstract Repetitive transcranial magnetic stimulation (rTMS) is an FDA-approved therapy in major depressive disorder. However, its treatment efficacy on depression after traumatic brain injury (TBI) remains inconclusive. We conducted a meta-analysis to assess the effectiveness of executing rTMS over dorsolateral prefrontal cortex (DLPFC) on depression, cognitive impairment and post-concussion syndrome in individuals with traumatic brain injury. This study contained seven randomized controlled trials that published before April 5, 2020 in PubMed, Embase, Scopus, Cochrane, and Web of Science databases. The rTMS had significant anti-depressant effect (SMD = 1.03, p = 0.02), but the effects dissipated at 1-month follow-up (SMD = 0.39, p = 0.62). In the subgroup analysis, only applying rTMS to left DLPFC area of post-TBI patients showed significant anti-depressant effect (SMD = 0.98, p = 0.04). Moreover, current data observed that rTMS on post-TBI patients possessed substantial improvement in visuospatial memory (SMD = 0.39, p < 0.0001), but wasn’t in processing speed (SMD = − 0.18, p = 0.32) and selective attention (SMD = 0.21, p = 0.31). In addition, the effect of rTMS is not superior to sham on postconcussion syndrome. In conclusion, the short-term antidepressant effect of left DLPFC rTMS in patients with TBI was significant. However, the effectiveness of rTMS on cognition and postconcussion syndrome in patients with post-TBI depression was limited.